Distância diacrónica automática entre variantes diatópicas do português e do espanhol - Pichel, José Ramom (2020)
The objective of this work is to apply a perplexity-based methodology to automatically calculate the cross-lingual distance between different historical periods of diatopic language variants. This methodology applies to an adhoc constructed corpus in original spelling, on a balanced basis of fiction and non-fiction, which measures the historical distance between European and Brazilian Portuguese on the one hand, and European and Argentinian Spanish on the other. The results show very close distances, both in original spelling and automatically transcribed spelling, between the diatopic varieties of Portuguese and Spanish, with slight convergences/divergences from the middle of the 20th century until today. It should be noted that the method is not supervised and can be applied to other diatopic varieties of languages.